2021
DOI: 10.1186/s12940-021-00761-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of air pollution exposure on social behavior: a synthesis and call for research

Abstract: Background There is a growing literature from both epidemiologic and experimental animal studies suggesting that exposure to air pollution can lead to neurodevelopmental and neuropsychiatric disorders. Here, we suggest that effects of air pollutant exposure on the brain may be even broader, with the potential to affect social decision-making in general. Methods We discuss how the neurobiological substrates of social behavior are vulnerable to air p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 170 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Hospital nursing administrators can reduce the risk of bloodborne occupational exposure by improving the medical environment and increasing the allocation of human resources [ 32 ]. Midwives should receive continuous training for a full range of occupational protection, thus improving and standardizing their occupational protection behaviors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital nursing administrators can reduce the risk of bloodborne occupational exposure by improving the medical environment and increasing the allocation of human resources [ 32 ]. Midwives should receive continuous training for a full range of occupational protection, thus improving and standardizing their occupational protection behaviors [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The University Corporation for Atmospheric Research (UCAR) reported that atmospheric variables such as temperature, air pressure, and humidity influence both weather and air quality [10]. "Air quality is strongly dependent on weather and is therefore sensitive to climate change [11].…”
Section: Effects Of Atmospheric Variables On Air Qualitymentioning
confidence: 99%
“…In particular, particulate matters with diameter less than 2.5 (PM 2.5 ) and diameter less than 10 (PM 10 ) have been reported for its adverse effect on human health, including respiratory diseases, cardiovascular diseases, diabetes, and neuropsychological outcomes such as depression [ 10 , 11 ]. Three explanations were introduced to understand the mechanism of depression: first, particulate matter enters the bloodstream and travels to the brain, where it causes neuroinflammation and oxidative stress, resulting in sadness [ 12 , 13 ]. Second, particulate matter inhibits physical activity, which is reported to be associated with depression [ 14 , 15 ], as well as social interaction.…”
Section: Introductionmentioning
confidence: 99%